2000
DOI: 10.1006/viro.2000.0212
|View full text |Cite
|
Sign up to set email alerts
|

Crosslink Analysis of N-Terminal, C-Terminal, and N/B Determining Regions of the Moloney Murine Leukemia Virus Capsid Protein

Abstract: To analyze contacts made by Moloney murine leukemia virus (M-MuLV) capsid (CA) proteins in immature and mature virus particles, we have employed a cysteine-specific crosslinking approach that permits the identification of retroviral Gag protein interactions at particular residues. For analysis, single cysteine creation mutations were made in the context of protease-deficient or protease-competent parental constructs. Cysteine creation mutations were chosen near the N- and C-termini of CA and at a site adjacent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 52 publications
2
19
0
Order By: Relevance
“…We find this hypothesis attractive because of the alternating positively and negatively charged bands on the proposed ␣-helices. In addition, cross-linking experiments indicated that the extreme C termini of the MLV CA domains are in close proximity with one another in immature virions (29). This observation is in agreement with the possibility that charged assembly helix motifs from different Gag polyproteins interact with one another.…”
Section: Discussionsupporting
confidence: 81%
“…We find this hypothesis attractive because of the alternating positively and negatively charged bands on the proposed ␣-helices. In addition, cross-linking experiments indicated that the extreme C termini of the MLV CA domains are in close proximity with one another in immature virions (29). This observation is in agreement with the possibility that charged assembly helix motifs from different Gag polyproteins interact with one another.…”
Section: Discussionsupporting
confidence: 81%
“…293T and HiL cell lines were passaged at 37°C in 5% CO 2 in culture medium containing Dulbecco's modified Eagle's medium supplemented with 10 mM HEPES (pH 7.4), penicillin, and streptomycin plus 10% fetal calf serum. For transfections, 10-cm plates of 293T cells were transfected by the calcium phosphate method (4,23,29,30,44,45) with either 24 g of HIVLuc DNA, 16 g of HIVLuc plus 8 g of pVSV-G DNA, or 12 g of HIVLuc plus 6 g of pVSV-G plus 6 g of BlaM-vpr DNA. Briefly, confluent 10-cm dishes of 293T cells were split 1:4 the day prior to transfection.…”
Section: Methodsmentioning
confidence: 99%
“…Purified fractions were desalted by buffer exchange in Sephadex G25 spin columns with 10 mM sodium phosphate (pH 7.8) and stored under nitrogen at Ϫ80°C. Purified (Ͼ95%) proteins at 0.8 to 3 mg/ml were evaluated after sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) (17,29,30,41,42), staining with 0.4% Coomassie blue R250 (Sigma) in 50% methanol-10% acetic acid, destaining in 50% methanol-10% acetic acid, and gel storage in 10% acetic acid. Proteins also were evaluated by immunoblotting.…”
Section: Methodsmentioning
confidence: 99%